The Influence of Occupational Health and Safety (K3), Work Experience on Employee Performance at PT. Telaga Hikmah Kebun Hikmah Satu, East Pedamaran District - Munawaroh, Siti; Rismansyah, Rismansyah; Arafat, Yasir (prodima@fe.uika-bogor.ac.id, 2023)
The company has prepare tool protection equipment work with appropriate as well as Fulfill provision K3 rules, however there is a number of employee still negligent use tool and equipment work by discipline moment work, thing this naturally have influence for company. Furthermore, there is employees who have not quite enough answer new ( position ), current doing Duty not yet in accordance hope because not yet have experience on position new so that results work not yet maximum. Study this aims to find out influence K3, experience work to performance employees. The method used on study this is method quantitative. We found on health and safety work (k3) has the effect is only positive and significant to performance employees, plus with experience work have his influence is positive also significant to perfor-mance employee and also added K3, experience work by together give influence only is positive and significant nsi to performance employees.